Fifteen novel immunoreactive proteins of Chinese virulent Haemophilus parasuis serotype 5 verified by an immunoproteomic assay - Yu, Yanfei; Wu, Guangyan; Zhai, Zhipeng; Yao, Huochun; Lu, Chengping; Zhang, Wei (Folia microbiologica, 2015)
Haemophilus parasuis (H. parasuis) is associated with meningitis, polyserositis, polyarthritis and bacterial pneumonia. At present, its prevention and control is difficult because of the lack of suitable subunit vaccines. Nowadays, high-throughput methods, immunoproteomics, are available to screen for more vaccine candidates. A protein extraction method for H. parasuis and two-dimensional electrophoresis (2-DE) were optimized to provide high-resolution profiles covering pH 3 to 10. Twenty immunoreactive spots were excised from gels after strict comparison between 2-DE Western blot membranes and the relevant gels. Matrix-assisted laser desorption/ionization-time of flight-mass spectrometry (MALDI-TOF-MS) and MALDI-TOF-TOF-MS successfully identified 16 different proteins. Fifteen of them were reported as immunoreactive proteins in H. parasuis for the first time. In addition, recombinant HP5-7 (ABC transporter, periplasmic-binding protein) showed immunoreactivity both with hyperimmune rabbit serum and convalescent swine serum. Four recombinants of the 14 successfully expressed genes showed immunoreactivity with hyperimmune rabbit serum.
Keywords: Haemophilus Infections; Rabbits; bakteriální proteiny; China; protilátky bakteriální; proteomika; Blotting, Western; Čína; Molecular Sequence Data; séroskupina; Proteomics; Serogroup; zvířata; Mass Spectrometry; 2D gelová elektroforéza; Swine Diseases; hmotnostní spektrometrie; Swine; nemoci prasat; hemofilové infekce; Electrophoresis, Gel, Two-Dimensional; prasata; Bacterial Proteins; molekulární sekvence - údaje; Haemophilus parasuis; Animals; western blotting; Antibodies, Bacterial; králíci